ADVANTAGES COMPETE SME BY USING FIVE FORCE PORTER IN DEALING WITH ASEAN ECONOMIC SOCIETY - Julita Julita, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study aims to find the problems that often inhibit the development of SMEs in Deli Serdang Regency in competitive advantage, especially in the face of MEA, for it needed a strategy in creating competitive advantage in the era of MEA. Many strategies for creating competitive advantage and one of Porter's generic strategies. This strategy provides success in the company so that researchers want to adopt Porter generic strategy for MSME especially in Deli Serdang Regency. This research uses research and development method, which becomes object in this research is 70 SMEs in Deli Serdang Regency.The method used in data collection is primary data (questionnaire) and secondary data (literature study). Data analysis was done descriptively.This research is the third year of research (final) which implemented the socialization of model and implementation of Excellence in competing UMKM by using five force porter in facing the ASEAN Economic Community.